When Gratitude Evokes Indebtedness. Issue 2 (5th February 2019) - Oishi, Shigehiro; Koo, Minkyung; Lim, Nangyeon; Suh, Eunkook M.
Abstract : Background: Research in the US found that gratitude increases happiness. We conducted three studies to examine whether gratitude increases happiness among Koreans, as well. Methods: Participants were randomly assigned to a gratitude or a control condition in Studies 1 and 2, and into a gratitude toward someone important or a gratitude toward own health condition in Study 3. Their moods were then measured. Results: Gratitude writing marginally significantly evoked indebtedness among Korean students (Study 1, N  =   336) but not among American students (Study 2, N  =   219). Equally important, even among Americans, those who wrote about their gratitude toward someone important reported feeling indebtedness marginally more than those who wrote about their gratitude toward something or someone not that important. In Study 3 ( N  =   181), American participants, randomly assigned to write about their gratitude toward someone important, reported not only more gratitude but also more indebtedness than those assigned to write about their gratitude toward their own health. Conclusions: Taken together, these studies suggest that gratitude evokes indebtedness when gratitude is about someone important.